Mutual influences between the main olfactory and vomeronasal systems in development and evolution - Suárez, Rodrigo; García-González, Diego; De Castro, Fernando (Frontiers in Neuroanatomy, 2012)
The sense of smell plays a crucial role in the sensory world of animals. According to a long-held view, the main olfactory system is specialised in the detection of environmental odorants, while the vomeronasal system senses semiochemicals produced by other individuals, traditionally known as pheromones. Although both systems differ in their anatomy and function, recent evidence suggests they act synergistically in the perception of scents. These interactions include similar responses to ligands, overlap of central connections and mutual influences in the regulation of olfactory-guided behaviour. In the present work, we propose the idea that the mutual influences between systems observed at the organismic level result from their constant interaction throughout ontogeny and phylogeny. We review the literature to illustrate examples of developmental and evolutionary processes that evidence these interactions and propose that future research integrating both systems may shed new light on the mechanisms of olfaction.